PENGARUH RASIO LIKUIDITAS, RASIO SOLVABILITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BEI TAHUN 2017-2020 - Maya Valentina Yulanda; Nadia Roosmalita Sari (Reinforce: Journal of Sharia Management, 2023)
Infrastructure companies are companies that contribute to development, this type of company also has good prospects, especially in the global capital market. So in this case a company wants its business to be sustainable and therefore always tries to manage its finances by obtaining, allocating and using it efficiently and effectively, as well as improving the quality of new products and investments. This study aims to determine the effect of liquidity, solvency and profitability on firm value in infrastructure sector companies listed on the Indonesia Stock Exchange in 2017-2020. The method used is a quantitative approach and multiple linear regression analysis, while for the determination of the sample using the purposive sampling method with certain criteria, the number of samples is 10 companies. Testing this data using SPSS 16 software. The results showed that liquidity had no effect on firm value, solvency had a significant effect on firm value, and profitability had a significant effect on firm value.